1991
DOI: 10.1071/wr9910677
|View full text |Cite
|
Sign up to set email alerts
|

Home Range and Activity Patterns of Red Foxes in Nadgee Nature Reserve.

Abstract: Three adult red foxes (Vulpes vulpes) in a 20-km2 wilderness area of coastal south-eastern Australia were studied during pre-denning and denning. Home ranges were defined by geographic featues, but not by roads. The foxes occupied exclusive home ranges, and observations suggest that they were territorial and existed alone or, at most, in mated pairs. Home-range sizes were small (1.2-5.2 km2) compared with those in North America and Europe, but similar to those in England and Wales. During denning the femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
3

Year Published

1994
1994
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 22 publications
5
26
3
Order By: Relevance
“…Some papers report of a higher activity during the day (Eguchi and Nakazono 1980, Phillips and Catling 1991, Lovari et al 1994. The diurnal activity of one female found in this study has a parallel in the inversion of activity rhythms shown by a female in Australia, attributed to breeding (Phillips and Catling 1991).…”
Section: Discussionsupporting
confidence: 72%
“…Some papers report of a higher activity during the day (Eguchi and Nakazono 1980, Phillips and Catling 1991, Lovari et al 1994. The diurnal activity of one female found in this study has a parallel in the inversion of activity rhythms shown by a female in Australia, attributed to breeding (Phillips and Catling 1991).…”
Section: Discussionsupporting
confidence: 72%
“…Data on home-range size and core-areas were analyzed using the Animal Movement SA version 2.0 in ArcView (version 3.3; ESRI). The minimum number of locations required to accurately assess the home-range size of the pack was estimated by plotting cumulative home-range sizes against the number of locations (i.e., asymptotic home-range; Philipps & Catling, 1991). Similar to Case Study 1, home-range values were calculated using the 100% minimum convex polygon (MCP) and the 95% fixed Kernel method while the 50% fixed-kernel method was used to estimate size and shape of the coreareas or centers of activity within home-ranges.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The minimum number of locations required to accurately assess the home-range size of each animal was estimated by plotting cumulative home-range sizes against the number of locations (i.e. asymptotic home-range; [28]). The minimum convex polygon (MCP; [29]) and the 95% fixed-kernel [30] methods were used to determine homerange areas.…”
Section: Data Collection and Analysesmentioning
confidence: 99%